The role green marketing and product knowledge in strengthening consumer purchasing decisions for compost fertilizer at Tegal District - Sari Wiyanti; Muhammad siddik Erdi Wicaksana (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the extent of the influence of green marketing and product knowledge in influencing the purchase decision of compost fertilizer from Dinas Lingkungan Hidup (DLH) of Tegal Regency. This research method uses a non probability sampling technique with incidental sampling method, the sample used was 100 respondents. The analysis technique used is Multiple Regression Analysis and t test, F test and coefficient of determination. The results of the study based on the t test obtained by Green Marketing on purchasing decisions, the tcount value is 8.290, which means tcount> ttable, namely 8.290> 1.661 with a sig value. 0.000 <0.05 means H1 is accepted. Product Knowledge on purchasing decisions obtained a tcount value of 5,288 which means tcount> ttable, namely 5,288> 1.661 with a sig value. 0.000 <0.05 means H3 is accepted. The results of the F test obtained an Fcount value of 114.927, meaning that Fcount> Ftabel or 114.927> 2.689 with a sign value of 0.000 <0.05, which means H3 is accepted. Green Marketing and Product Knowledge have a positive and distributed effect simultaneously on consumer purchasing decisions for compost fertilizer from the Dinas Lingkungan Hidup (DLH) Tegal Regency.